2021
DOI: 10.1093/mnras/stab1307
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band spectral and timing properties of MAXI J1348–630 using AstroSat and NICER observations

Abstract: We present broadband X-ray spectral-timing analysis of the new Galactic X-ray transient MAXI J1348–630 using five simultaneous AstroSat and NICER observations. Spectral analysis using AstroSat data identify the source to be in the soft state for the first three observations and in a faint and bright hard state for the next two. Quasi-periodic oscillations at ∼0.9 and ∼6.9 Hz, belonging to the type-C and type-A class are detected. In the soft state, the power density spectra are substantially lower (by a factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The disc inclination angle, constrained at i = 32.9 +4.1 −0.6 degrees, The three soft state observations are spectrally similar without showing any significant difference in the parameter values (Table 4). On the other hand, Jithesh et al (2021) shows that there are significant differences in the power density spectra of the three observations in the LAXPC (3-15 keV) band. In fact, different segments of the Data2 have significantly different variability amplitude.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The disc inclination angle, constrained at i = 32.9 +4.1 −0.6 degrees, The three soft state observations are spectrally similar without showing any significant difference in the parameter values (Table 4). On the other hand, Jithesh et al (2021) shows that there are significant differences in the power density spectra of the three observations in the LAXPC (3-15 keV) band. In fact, different segments of the Data2 have significantly different variability amplitude.…”
Section: Discussionmentioning
confidence: 85%
“…They estimated the spin, black hole mass and inclination of the source by fixing the distance to 2.2 kpc, and the values were found to be 0.80 ± 0.02, 8.7 ± 0.3 M and 36.5 ± 1.0 degrees, respectively. Jithesh et al (2021) used five simultaneous AstroSat and NICER observations for studying the broadband X-ray spectral-timing properties of the source. They noted the presence of quasi-periodic oscillations of type-C and type-A classes and further via power density spectrum and energy-dependent rms, they confirmed that the disc is significantly less variable than the Comptonization component.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…bool et al 2019; Jithesh et al 2019;Mudambi et al 2020;Jithesh et al 2021). Flux resolved spectroscopy using sensitive instruments like NuSTAR for a larger sample of AGN with more continuous monitoring, will reveal the nature of the variability of these sources.…”
Section: Discussionmentioning
confidence: 99%
“…Spectro-timing properties of a new black hole transient MAXI J1348-630 have been investigated using the simultaneous/quasi-simultaneous AstroSat and NICER observations. The analysis revealed several interesting characteristics of the source, including the flip-flop behaviour, different types of QPOs and energydependent behaviour of variability components (Jithesh et al 2021). The detailed broadband spectral study using the reflection models constrained the spin and inclination of the system and the values are > 0.97 and ∼ 33 • , respectively (Mall et al 2023).…”
Section: Introductionmentioning
confidence: 96%